Twitter Visualitation of Healty Catering Food Promotion Strategy - Nafis, Khilyatun; Ambarwati, Rita; Pebrianggara, Alshaf (Fakultas Ekonomi Universitas Kadiri, 2024)
This analysis aims to determine whether there are differences in marketing strategies and which strategy is superior between the two health catering industries. Intermediary of Twitter as a place to retrieve data, where Twitter is a social media with the fastest spread of news through hashtags and trending topics of a phenomenon that is busy being discussed. They use qualitative methods by utilizing Social Network Analysis (SNA) and are assisted by several supporting tools such as Gephi, Wordji, Notepad++, and Dictionaries to make it easier for researchers to analyze the data obtained so that it is concrete and relevant. From the visualization of Twitter user tweet data, the researcher found that Twitter users discussed Yellowfit Kitchen health catering more than Gorygourmet, as evidenced by a large number of data visualizations obtained. Then on average, customers choose to subscribe to health catering Yellowfit Kitchen with the pure aim of dieting. At the same time, healthy catering Gorygourmet customers subscribe to a more nutritious diet to avoid disease.